Transformasi Pembelajaran Geometri: Dari Alat Peraga Fisik Ke Interactive Flat Panel (IFP) di Sekolah Dasar - Aryadi Nursantoso (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to explore the pedagogical transformation of teachers in geometry learning in elementary schools, shifting from the use of conventional physical manipulatives to Interactive Flat Panel (IFP) technology. Using a qualitative approach with a case study design, this research involved three elementary school teachers as key informants selected through purposive sampling. Data were collected through in-depth interviews and documentation studies, then analyzed using the Miles and Huberman model, which includes data condensation, data display, and conclusion drawing. The results show that IFP transforms geometry learning through three main aspects: (1) enhancing spatial visualization from static to dynamic, which facilitates the understanding of geometric shapes; (2) shifting the teacher's role into a digital laboratory facilitator; and (3) increasing mathematical precision compared to physical manipulatives. However, challenges such as time management and potential technological distractions remain. This study concludes that IFP effectively accelerates students' geometric thinking stages according to Van Hiele's theory through 3D object manipulation features. The implications of this research emphasize teacher training to optimize IFP potential in the classroom